'It was quite a shock': A qualitative study of the impact of organisational and personal factors on newly qualified nurses' experiences. Issue 15 (5th May 2021) - Ho, Szu‐Szu; Stenhouse, Rosie; Snowden, Austyn
Abstract: Aims and objectives: To explore how newly qualified nurses' work experiences are constructed through the interplay between self, workplace and home‐life influencing their retention. Background: Nurses are critical to achieving the goal of universal health coverage. However, shortages of nursing staff are endemic. Of particular concern, newly qualified nurses are more likely to leave the nursing workforce. The point of transition to working as a newly qualified nurse is a time of vulnerability. Most studies attempt to discover why nurses leave. This study uses the concept of job embeddedness to examine the experience of this transition and first two years of practice to understand what might help newly qualified nurses stay. Design: Qualitative approach using semi‐structured telephone interviews. Methods: Self‐selecting sample of nurses ( n  = 23) who participated 1‐year ( n  = 12) and 2 years ( n  = 11) post‐qualification. Participants were part of a larger longitudinal cohort ( n  = 867) study which has followed them since September 2013 when they entered nurse education in two Scottish universities. Thematic analysis was used to understand the interplay between organisation/workplace and the individual. Results: Three themes were developed: transition shock; workplace factors and work/life balance. Two further subthemes were developed: experience of support and belonging; and feeling unsupported and alienated. Eight participants had changed job or left, and two were looking to leave nursing. Conclusion: This study highlights how the experience of transition shock can be positively or negatively impacted by the workplace environment, and how in turn this impacts the home environment. Ultimately, this impacts retention of newly qualified nurses. Relevance to clinical practice: Having adequate support resources, such as staffing, supportive team morale, professional development and family‐friendly work environment, can create a work environment where they feel the purpose and meaningfulness of working as a nurse. This 'job embeddedness' can potentially enhance nurse retention. Reporting follows the COREQ checklist.